The efficacy of life skills training on the improvement and prevention of relapse of people with drug abuse - Baha Amini; Karim Afshar Nia (مجله علوم روانشناختی, 2023)
Background: One of the effective treatments for the recovery of people with drug abuse is the treatment of life skills training. There are few studies on the effect of life skills training on the recovery and prevention of relapse of drug abusers. Aims: The purpose of this study was to determine the effectiveness of life skills training on the recovery and prevention of relapse in drug abusers Methods: The method of the present research was an experimental type with a design (pre-test-post-test with a control group). The statistical population of the present study consisted of all people with drug abuse in addiction treatment centers (methadone maintenance treatment) (MMT) who were being treated in Kermanshah city from 2016 to 2018. The research sample consisted of 60 people (30 people in the experimental group and 30 people in the control group) who were randomly assigned to two experimental and control groups using the available multi-stage method. The experimental group was exposed to the independent variable (life skills) in 7 sessions of 90 minutes, then both groups were given a post-test and a follow-up was done one month later. Data were analyzed using SPSS-21 software and multivariate covariance analysis (MANCOVA). Results: The results obtained for the relapse prevention and recovery variables were significant at P≥ 0.001 level Conclusion: According to the results of the present study, it can be said that life skills training is effective on the variable of relapse prevention and recovery of people with drug abuse and this type of treatment can be used to improve people with drug abuse.